2011
DOI: 10.2527/jas.2010-3041
|View full text |Cite
|
Sign up to set email alerts
|

Fresh meat and further processing characteristics of ham muscles from finishing pigs fed ractopamine hydrochloride

Abstract: Ractopamine hydrochloride (RAC) has consistently led to an advantage in carcass cutting yields of finishing pigs and remains a common feed additive in US finishing pig diets. Less is known about the effect of RAC on further processing characteristics. Some researchers have reported advantages in ultimate pH of the LM in pigs fed RAC. If a greater ultimate pH was also observed in hams, the increased pH could affect further processing characteristics and lead to better protein interaction and improved textural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…However, reductions in fat deposition induced by ractopamine have not been clearly observed (Dunshea et al 1993(Dunshea et al , 1998Carr et al 2005b;Fernández-Dueñas et al 2008;Moore et al 2009;Boler et al 2010;Kutzler et al 2010). Because literature reports regarding the effects of ractopamine on fat accretion are inconclusive, in vitro assays were developed to explain the possible irresponsiveness of ractopamine in adipose tissue metabolism.…”
Section: Modulation Of Lipid Metabolism By Ractopaminementioning
confidence: 99%
See 1 more Smart Citation
“…However, reductions in fat deposition induced by ractopamine have not been clearly observed (Dunshea et al 1993(Dunshea et al , 1998Carr et al 2005b;Fernández-Dueñas et al 2008;Moore et al 2009;Boler et al 2010;Kutzler et al 2010). Because literature reports regarding the effects of ractopamine on fat accretion are inconclusive, in vitro assays were developed to explain the possible irresponsiveness of ractopamine in adipose tissue metabolism.…”
Section: Modulation Of Lipid Metabolism By Ractopaminementioning
confidence: 99%
“…Consumer demand for leaner and healthier pork products has risen steadily each year; thus, improvements in animal health, genetics, and especially nutritional technologies, such as the utilization of β-adrenergic agonists in diets, have become important in helping pork producers to meet this demand. In addition to their use in human and veterinary medicine as bronchodilatory and tocolytic agents (Kuiper et al 1998), β-adrenergic agonists increase both lean growth rate and carcass lean percentage (Boler et al 2010), and improve feed efficiency of finishing pigs (Rikard-Bell et al 2009;Hinson et al 2011). Ractopamine is classified as a β-adrenergic agonist that acts as a repartitioning agent, redirecting nutrients away from adipose tissue and towards greater muscle deposition.…”
Section: Introductionmentioning
confidence: 99%
“…These results favor the addition of ractopamine in pig diets, considering that the use of β agonists could cause a high level of stress to the animal and develop PSE meat (Pale, Soft and Exudative) or stimulate glycolysis, thereby promoting ante-mortem muscular glycogen consumption, resulting in accumulation of lactic acid in the carcass after slaughter (Boler et al, 2010), which would be detected by a pH decrease, not observed in the present study.…”
Section: Resultsmentioning
confidence: 58%
“…It is well documented that dietary ractopamine increases carcass weight in finishing pigs (Stites et al, 1991;Armstrong et al, 2004;Fernandez-Duenas et al, 2008). Furthermore, an increase in the weight of inside ham (consisting of semimembranosus muscle) was observed in ractopamine-fed pigs (Boler et al, 2011). The increased muscle growth due to ractopamine could possibly demand increased levels of plasma membrane repair proteins to maintain homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Ractopamine is a beta-agonist approved for use in swine industry to increase growth rate, feed efficiency, carcass yield, and leanness in finishing pigs (Apple et al, 2007;Dunshea, 2012;Pompeu et al, 2017) in more than 25 countries, including the United States, Canada, Australia, Mexico, Philippines, Brazil, sand South Korea (AMI, 2012). Dietary ractopamine increases leanness (Boler et al, 2011) and carcass weight (Stites et al, 1991;Armstrong et al, 2004;Fernandez-Duenas, 2008;Needham & Hoffman, 2015) in pigs, and the increased carcass weight is a consequence of the increase in myofibrillar protein synthesis (Adeola et al, 1992).…”
Section: Introductionmentioning
confidence: 99%